Double poling technique excelling models customizable to elite cross-country skiers` model characteristics - Mikhaylovskiy, S. P.; Gromov, M. M.; Selyukin, D. B. (Theory and Practice of Physical Culture, 2019)
Modern cross-country skiing techniques are increasingly dominated by the double poling technique whenever practical on the competitive tracks. Some competitive distances are run today by the classical double poling technique only and without a friction ski wax. The study was designed to develop and test benefits of a double poling technique perfection technology for competitive success using Concept 2 SkiErg training machine equipped with a semi-automatic control system customizable to the elite cross-country skiers` model characteristics. The new double poling technique perfection technology testing experiment was run at Kavgolovo Training Center in Toksovo town. Sampled for the Experimental and Reference Group were students of Lesgaft National State University of Physical Education, Sport and Health majoring in the Skiing Sport Training Theory and Practice.